The Relationship between Obesity and the Incidence of Hypertension in Young Adults (18-40 Years) in Tomohon City in 2019 - Jonesius Eden Manoppo1 , Andi Zulkifli Abdullah2 , Citra Kesumasari2 , Ridwan Mochtar Thaha2 , Sri A (Institute of Medico-legal Publications Pvt Ltd, 2020)
Hypertension is an unfinished health problem until now. Hypertension is a disease that causes stroke anddecreases the quality of life. One of the preventable causes of hypertension is obese. The purpose of thisstudy is observing the relationship between nutritional status, in this case obesity, and the incidence ofhypertension in young adults (18-40 years) in Tomohon City. By utilizing a cross sectional approach,this research was conducted in January-December 2019 on young adults aged 18-40 years who visited 7community health centers in Tomohon. There were 4,040 samples who were willing to be involved in thisstudy, who had never previously been diagnosed with hypertension by a doctor in any health facility. Basedon the Pearson’s chi-square test showed a p-value of age and the incidence of hypertension is 0.0001 < 0.05with estimated risk of 2.206 (CI 95%: 1.917-2.593). P-value of gender and the incidence of hypertension is0.0001 < 0.05 with estimated risk of 0.715 (CI 95%: 0.622-0.823). P-value of obesity and the incidence ofhypertension is 0.0001 < 0.05 with estimated risk of 2.502 (CI 95%: 2.150-2.911). So, it can be concludedthat there is a significant relationship between obesity and the incidence of hypertension